Enhancing quality of higher education for graduate research students development - Zainal Abiddin, Norhasni; Ismail, Affero; Taniredja, Tukiran (ASPENSI, 2013)
Quality education becomes a major issue in higher education. The numbers of graduate students to pursue their higher education keep increasing by years. In the meantime, the institutions of higher learning are striving to attract more students, especially at the graduate level by making every effort to provide quality education. Graduate students contribute to the development of research outcome. Some scholars proposed that the strategic success of a service organization depends on its ability to consistently meet or exceed customer service expectations. A constant effort should be made to ensure the customer satisfaction. This paper provides the relevant input for effective resource development in institutional of higher education. The approach would address the needs of students further along the process with an emphasis on data gathering, management and analysis, compiling a thesis or dissertation, assessment, and the publishing of research results. Another approach would relate to generic aspects of graduate growth, development, and progress. Conceptual evidence is presented which combination of resource needs to focus. It is hoped to contribute a proper insight of effective resource in developing distinguished human capital.